Kekerasan Fisik dalam Rumah Tangga Perspektif Hukum Islam - Ibnu Amin; Dudung Abdul Razak; Faisal Efendi; Widia Sulastri (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This study aims to explore the extent to which the relevance of Islamic legal norms to the spirit of non-violence, especially in the household, considering that the topic of domestic violence is not a specific discussion or has received little attention in discussions on Islamic law. This study uses a normative juridical approach. Data was collected using documentation techniques on Islamic legal literature, in the form of fiqh books, as well as the texts of the Koran and Hadith. This study shows that acts of domestic violence are prohibited in Islam. Islamic law in this topic is very relevant to the spirit of non-violence and laws and regulations in Indonesia related to acts of violence, both in general and in the family context.